Service on board an aircraft as an instrument of shaping the image of air carriers - Tłoczyński, Dariusz (Obsługa na pokładzie samolotu jako instrument kształtowania wizerunku przewoźników lotniczych, 2020)
As a result of activities on the competitive air transport market, operators provide innovative products that are designed to achieve the company’s objectives. In addition to the typical services offered, the human capital management process plays an important role in attracting new passengers. One of the elements of shaping the air carrier’s image is inflight service. After the journey, the passenger assesses all elements, at the same time stating that on-board service, despite being carried out at a high quality level, is not a factor clearly influencing the decision to purchase an air service. As a result of the author’s own marketing research at Polish airports, using a direct interview, it was found that in-flight service has a neutral effect on the decision to choose an air carrier. This situation shows that there is a need to conduct research assessing what elements and to what extent they influence the decision to choose an air carrier
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 183-194
Keywords: air transport; cabin crew; air cariers; flight attendant; transport service; on-board service; transport lotniczy; załoga pokładowa; przewoźnicy lotniczy; stewardesa; steward; usługa przewozowa; serwis pokładowy